EFFECT OF SUPPLEMENTATION OF CONCRALS, GnRH AND PGF2alpha ON POSTPARTUM REPRODUCTION IN BUFFALOES - PATEL, P P; PANCHAL, M T; PATEL, B N; KAVANI, F S (The Indian Journal of Animal Reproduction, 2023)
A total of 107 advance pregnant buffaloes were studied for their postpartum fertility. Among the buffaloes studied, the incidences of anoestrus and sub-oestrus were found to be 15.74 and 15.74 per cent, respectively. The mean days of calving to first postpartum oestrus (FPPE) and service period for treatment groups: T-I (Concentrate and minerals supplementation), T-11 (GnRH), T-111 (PG) and IV (Control) group were found to be 52.70±1.85 (47.25 to 58.15), 76.18±3.14 (66.84 to 85.52), 62.94± 0.29 (range 53.60 to 72.28) and 115.96 ±7.25 (107.93 to 123.99), and 60.26±2.75 (53.62 to 66.89), 91.00±6.25 (85.86to 109.34), 88.90±7.94 (range 74.52to 103.28)and 112.24±2.75(101.20to 123.26), respectively, both parameters differing significantly (p<0.01) between groups. The overall per cent CRs and number of services per conception for treatment groups: T-I, T-11, T-111 and control buffaloes were found to be 94.00, 76.47, 64.70 and 58.33, and 1.25, 3.27, 2.38 and 3.42, respectively, both differing significantly (p<0.01) between groups. It was concluded that there was a beneficial effects of pre- and post-partum concentrate and minerals feeding in the rural buffaloes in view of resumption of postpartum ovarian activity within the period of 55 days· and conceived by 65 days. However, some of the animals still - suffered with postpartum anoestrus and subestrus conditions, which could be settled successfully using GnRH and PG, respectively.